Humanistic Da’wah Literacy Among Z Generation: An Analysis of the Communication of Islamic Humanist Values on TikTok and Instagram via the @kadamsidik00 Account - Sari, Rahmita; Islami, Nafa Aqla; Jariah, Ainun; Yuliantina, Devi; Asmianur, Refa (Ishlah: Jurnal Ilmu Ushuluddin, Adab dan Dakwah, 2026)
The development of digital media has transformed Islamic da’wah practices, making them more interactive and aligned with the characteristics of the Z Generation that has grown up in a digital ecosystem. This study focuses on the patterns of humanistic da’wah developed by Z Generation da’wah creators through social media. The research problem lies in the limited existing studies on how Z Generation creators construct, communicate, and internalize the values of Islamic humanism through digital platforms such as TikTok and Instagram. This study employs a qualitative method with a netnographic approach to observe the activities, content, and digital interactions on the Kadam Sidik (@kadamsidik00) da’wah account on TikTok and Instagram. Data was collected through observations of content posts, communication patterns, and audience responses, which were then analyzed thematically. The results indicate that the applied da’wah patterns reflect a humanistic approach through the use of language that is communicative, empathetic, non-judgmental, and relevant to the emotional experiences of the Z Generation. The dominant values of Islamic humanism include empathy, tolerance, equality, and respect for human dignity. The communication strategies employed are dialogic, creative, and participatory, thereby fostering an emotional connection between the preacher and the audience. These findings indicate that the success of digital da’wah among Z Generation is determined not only by religious content but also by the ability to integrate a humanistic approach with digital communication strategies that align with the characteristics of the young audience. Perkembangan media digital telah mengubah praktik dakwah Islam menjadi lebih interaktif dan dekat dengan karakteristik Generasi Z sebagai kelompok yang tumbuh dalam ekosistem digital. Penelitian ini berfokus pada pola dakwah humanis yang dikembangkan oleh kreator dakwah Generasi Z melalui media sosial. Permasalahan penelitian terletak pada masih terbatasnya kajian mengenai bagaimana kreator Generasi Z membangun, mengomunikasikan, dan menginternalisasikan nilai-nilai humanisme Islam melalui platform digital seperti TikTok dan Instagram. Penelitian ini menggunakan metode kualitatif dengan pendekatan netnografi untuk mengamati aktivitas, konten, dan interaksi digital pada akun dakwah Kadam Sidik (@kadamsidik00) di TikTok dan Instagram. Data dikumpulkan melalui observasi terhadap unggahan konten, pola komunikasi, serta respons audiens yang kemudian dianalisis secara tematik. Hasil penelitian menunjukkan bahwa pola dakwah yang diterapkan mencerminkan karakter dakwah humanis melalui penggunaan bahasa yang komunikatif, empatik, tidak menghakimi, dan relevan dengan pengalaman emosional Generasi Z. Nilai-nilai humanisme Islam yang dominan meliputi empati, toleransi, kesetaraan, dan penghormatan terhadap martabat manusia. Strategi komunikasi yang digunakan bersifat dialogis, kreatif, dan partisipatif sehingga mampu membangun kedekatan emosional antara dai dan audiens. Temuan ini menunjukkan bahwa keberhasilan dakwah digital pada Generasi Z tidak hanya ditentukan oleh substansi keagamaan, tetapi juga oleh kemampuan mengintegrasikan pendekatan humanis dan strategi komunikasi digital yang sesuai dengan karakteristik audiens muda.